Evaluation of crack bridging in adhered waterproofing systems - Santos, Julie Anne Braun dos (2021)
Waterproofing systems adhered to concrete structures produce a protective barrier against fluids and aggressive agents' penetrations. However, if cracks appear in the substrate and are transmitted to the adhered waterproof layer, the system's water tightness can be compromised. This work aims to perform an experimental evaluation of two waterproofing membranes' behavior, based on acrylic, when adhered to concrete substrates subject to cracking. A mechanical test method based on indirect tensile stress associated with Digital Image Correlation analysis (DIC) is proposed to assess the transfer of cracks from concrete substrates to bonded waterproofing membranes. The results showed that this methodology allows distinguishing the membranes' behavior concerning the transfer of cracks. It was also possible to measure quantitatively, with the DIC technique, the degree of crack in the concrete that resulted in cracking in the membranes. The pure acrylates membrane resulted in less stress dissipation from the substrate than the acrylic copolymer without cement membrane. This behavior can be related to the difference in the elongation of the materials. The adhesion of the membranes to the substrate was high and considerably higher than the normative requirements, and can be associated with the membrane's difficulty in dissipating the substrate stress, cracking more easily.